Membangun Iman dalam Era Digital: Peran Media Sebagai Alat Evangelisasi Kontemporer - Koli, Arnoldus Nofrianus (Borneo Review, 2025)
This study aims to analyze the role of digital media in building the faith of Christians and how media can be effectively utilized as a tool of evangelization in the contemporary era. The main problem studied is the extent to which digital media can be a relevant and impactful means of evangelization in the faith life of modern society, especially the younger generation who are familiar with technology. The method used in this research is a qualitative approach with data collection techniques through literature studies, observation of religious digital content, and in-depth interviews with digital ministry actors, such as priests, Catholic content creators, and active social media users. The results show that digital media has great potential in delivering messages of faith creatively, quickly, and widely. However, its effectiveness is highly dependent on the quality of the message, the cultural context of the users, and the active involvement of the ecclesial community. This research confirms that media is not just a tool, but can become a new spiritual encounter space that supports the evangelization process in the digital world.